2017
DOI: 10.1007/s00262-017-2020-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-derived interleukin-1beta promotes human breast cancer cell migration and lymphatic adhesion in vitro

Abstract: Lymphovascular invasion (LVI), encompassing blood and lymphatic vessel invasion, is an important event in tumourigenesis. Macrophages within the tumour microenvironment are linked to the presence of LVI and angiogenesis. This study investigates the role of macrophage-derived, caspase-1-dependent interleukin-1beta (IL-1β) in an in vitro model of LVI. IL-1β significantly augmented the adhesion and transmigration of breast cancer cell lines MCF7 and MDA-MB-231 across endothelial cell barriers. MDA-MB-231 and MCF7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…An in vitro study showed that treatment of endothelial cells with recombinant IL‐1β stimulated the adhesion of breast tumor cells to blood and lymphatic endothelial cells; in addition, it enhanced the transmigration of tumor cells. These data suggest that IL‐1β is likely to be involved in lymphatic vessel invasion by breast cancer …”
Section: Il‐1 and Malignanciesmentioning
confidence: 79%
See 1 more Smart Citation
“…An in vitro study showed that treatment of endothelial cells with recombinant IL‐1β stimulated the adhesion of breast tumor cells to blood and lymphatic endothelial cells; in addition, it enhanced the transmigration of tumor cells. These data suggest that IL‐1β is likely to be involved in lymphatic vessel invasion by breast cancer …”
Section: Il‐1 and Malignanciesmentioning
confidence: 79%
“…These data suggest that IL-1β is likely to be involved in lymphatic vessel invasion by breast cancer. 158 Cervical cancer is the second most prevalent malignancy in women. 159 A high susceptibility to cervical cancer in women with of IL1RN VTNR polymorphism was observed in different ethnic groups.…”
Section: Il-1 and Malignanciesmentioning
confidence: 99%
“…This was sustained by the fact that inhibition or invalidation of NLRP3 in macrophages inhibited the metastatic potential of B16F10 murine melanoma cells in vitro [ 212 ]. Finally, macrophage-derived IL-1β was shown to regulate breast carcinoma cell migration and their adhesion to, and transmigration across, blood and lymphatic endothelial cells [ 213 ]. Cancer cells and fibroblasts can interact with each other to regulate cancer cell migration.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…This has led to the discovery of abundant circRNA expression in a variety of eukaryotic organisms. [ 46 ] RT-PCR is the easiest and fastest way to identify circRNA. Primers designed for circRNA reverse splice site sequences allow amplification and quantification of specific circRNAs.…”
Section: Research Methods Of Circrnamentioning
confidence: 99%